Care of patients with ST-elevation myocardial infarction: an international analysis of quality indicators in the acute coronary syndrome STEMI Registry of the EURObservational Research Programme and ACVC and EAPCI Associations of the European Society of Cardiology in 11 462 patients - Ludman, Peter; Zeymer, Uwe; Danchin, Nicolas; Kala, Petr; Laroche, Cécile; Sadeghi, Masoumeh; Caporale, Roberto; Shaheen, Sameh Mohamed; Legutko, Jacek; Iakobishvili, Zaza; Alhabib, Khalid F; Motovska, Zuzana; et al. (European heart journal. Acute cardiovascular care, 2023)
AIMS: To use quality indicators to study the management of ST-segment elevation myocardial infarction (STEMI) in different regions. METHODS AND RESULTS: Prospective cohort study of STEMI within 24 h of symptom onset (11 462 patients, 196 centres, 26 European Society of Cardiology members, and 3 affiliated countries). The median delay between arrival at a percutaneous cardiovascular intervention (PCI) centre and primary PCI was 40 min (interquartile range 20-74) with 65.8% receiving PCI within guideline recommendation of 60 min. A third of patients (33.2%) required transfer from their initial hospital to one that could perform emergency PCI for whom only 27.2% were treated within the quality indicator recommendation of 120 min. Radial access was used in 56.6% of all primary PCI, but with large geographic variation, from 76.4 to 9.1%. Statins were prescribed at discharge to 98.7% of patients, with little geographic variation. Of patients with a history of heart failure or a documented left ventricular ejection fraction ≤40%, 84.0% were discharged on an angiotensin-converting enzyme inhibitor/angiotensin receptor blocker and 88.7% were discharged on beta-blockers. CONCLUSION: Care for STEMI shows wide geographic variation in the receipt of timely primary PCI, and is in contrast with the more uniform delivery of guideline-recommended pharmacotherapies at time of hospital discharge.
Keywords: infarkt myokardu s elevacemi ST úseků; kardiologie; Stroke Volume; ST Elevation Myocardial Infarction; Cardiology; výsledek terapie; registrace; Prospective Studies; funkce levé komory srdeční; Quality Indicators, Health Care; Registries; tepový objem; Quality indicators; Guidelines; Observational studies; Humans; prospektivní studie; Primary percutaneous coronary intervention; ukazatele kvality zdravotní péče; koronární angioplastika; Percutaneous Coronary Intervention; Registry; akutní koronární syndrom; ST-segment elevation myocardial infarction; Treatment Outcome; Acute Coronary Syndrome; Reperfusion therapy; lidé; Ventricular Function, Left